Influence of made with renewable energy appeal on consumer behaviour. Issue 1 (25th October 2017) - Mydock III, Suni; Pervan, Simon James; Almubarak, Alanoud F.; Johnson, Lester; Kortt, Michael
Abstract : Purpose: The purpose of this paper is to explore the extent to which consumer purchasing behaviour is influenced by advertised information that a product is made with renewable energy. It also seeks to identify why some consumers might respond more favourably. Design/methodology/approach: Three experiments were conducted using two samples of university students enroled in Australia. The first experiment tested the main effect of this research, the second tested the potential amplifying effect of locus of control and the third tested the temporal orientation. Findings: Consumer respond favourably to products promoted as made with renewable energy. The possible explanation for this is that future temporal orientation (FTO) influences attitude towards the brand, attitude towards the advertisement, purchase intention and willingness to pay a premium for brands. The observed interaction effect between perceived greenness of the advertisement and FTO is also robust to scepticism. Research limitations/implications: Results presented here are also derived from responses made by students at a regional Australian university. Although atypical in their profile with most over 30 years of age, findings cannot reliably be generalised to the larger population. Determining how much importance a renewable energy appeal has when it is positioned among other green appeals would reveal the relative usefulness of the focal promotion to marketers. Practical implications: Promoting a firm's use of renewable energy presents an important opportunity to achieve desirable outcomes, and the efficacy of this is magnified within individuals that habitually focus on the future. Social implications: These findings benefit society because they contribute towards increasing the frequency of sustainable business practices. It should also encourage policy-makers to implement policy changes (e.g., removing subsidies that prevent renewable energy from attaining cost parity with non-renewable sources of energy), which can result in beneficial economic outcomes. Originality/value: This research is the first of its kind to be conducted in an Australian context, providing findings that assist both firms' and policy-makers' decision-making.